Dance Dramaturgy Modes of Agency, Awareness and Engagement - Hansen, Pil.; Callison, Darcey; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Ten international dramaturg-scholars advance proposals that reset notions of agency in contemporary dance creation. Dramaturgy becomes driven by artistic inquiry, distributed among collaborating artists, embedded in improvisation tasks, or weaved through audience engagement, and the dramaturg becomes a facilitator of dramaturgical awareness.
Keywords: Performing arts; Dance; Arts; Performing Arts; Dance; Arts